Avoiding misdiagnosis of duodenal papilla adenocarcinoma in a situs inversus totalis patient via laparoscopic pancreaticoduodenectomy: A rare case report - Liang, Hao; Wu, Ya-kun; Pang, Wu; Chen, Ming-liang; Zhu, Yu (Frontiers in Surgery, 2023)
Situs inversus totalis is a rare congenital anatomical anomaly that causes some difficult problems for surgeons when performing an operation. However, without histopathology specimens from surgery, a misdiagnosis of cancer may be unavoidable, in addition to affecting the improvement of prognosis. This study reports a rare patient with situs inversus totalis who presented with the main complaints of pruritus and vague abdominal pain. She was first misdiagnosed with cholangiocarcinoma and was finally diagnosed with duodenal papilla adenocarcinoma via laparoscopic pancreaticoduodenectomy. Situs inversus totalis was not a contraindication for surgery. Skilled surgeons and complete preparation during the perioperative period are two important keys to successful surgeries. Performing laparoscopic pancreaticoduodenectomy for patients with situs inversus totalis to avoid misdiagnosis of cancer and tailor appropriate therapy plans is cost-effective.